2011
DOI: 10.1007/s00348-010-1030-x
|View full text |Cite
|
Sign up to set email alerts
|

High-speed stereoscopic PIV study of rotating instabilities in a radial vaneless diffuser

Abstract: This paper presents an experimental analysis of the unsteady phenomena developing in a vaneless diffuser of a radial flow pump. Partial flow operating conditions were investigated using 2D/3C high repetition rate PIV, coupled with unsteady pressure transducers. Pressure measurements were acquired on the shroud wall of the vaneless diffuser and on the suction pipe of the pump, whereas PIV flow fields were determined on three different heights in the hub to shroud direction, inside the diffuser. The classical Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
7
25
0
Order By: Relevance
“…They employed a two equation isotropic turbulence model. The numerical result was found in good agreement with observed pressure fluctuations and number of rotating stall cells as compared with particle imaging velocimety (PIV), see [13]. However, it was concluded that the numerical result using isotropic turbulence modeling underestimates the strength of the rotating stall vortex as compared with PIV measurements.…”
Section: Introductionsupporting
confidence: 66%
“…They employed a two equation isotropic turbulence model. The numerical result was found in good agreement with observed pressure fluctuations and number of rotating stall cells as compared with particle imaging velocimety (PIV), see [13]. However, it was concluded that the numerical result using isotropic turbulence modeling underestimates the strength of the rotating stall vortex as compared with PIV measurements.…”
Section: Introductionsupporting
confidence: 66%
“…(2) Experimental researches (for example: PIV study-Wuibaut, Dupont, Bois, Caignaert, & Stanislas, 2002;Krause, Zähringer, & Pap, 2005;Pavesi et al, 2011;Dazin et al, 2008Dazin et al, , 2011 and numerical analyses are quite numerous in open literature. The main research contents of rotating stall were focused on several aspects: i.…”
Section: Introductionmentioning
confidence: 99%
“…Details on PIV techniques used, experimental setup, and result interpretations can be found in the Ref. [19]. The experimental procedure allowed the determination of the mean absolute velocities for up to 7 impeller angular positions relative to diffuser vanes, as shown in Fig.…”
Section: Comparison With Piv Measurementmentioning
confidence: 99%